Normative Grundlagen des pluralistischen Paradigmas - Haker, Christoph (Kieler sozialwissenschaftliche Revue. Internationales Tönnies-Forum)

Oxygen‐dependent Photoluminescence and Electrical Conductance of Zinc Tin Oxide (ZTO): A Modified Stern‐Volmer Description - Kothe, Linda; Klippstein, Josefin; Kloß, Marvin; Wengenroth, Marc; Poeplau, Michael; Ester, Stephan; Tiemann, Michael (ChemPhysChem)
Zinc tin oxide (ZTO) is investigated as a photoluminescent sensor for oxygen (O2); chemisorbed oxygen quenches the luminescence intensity. At the same time, ZTO is also studied as a resistive sensor; being an n‐type semiconductor, its electrical conductance decreases by adsorption of oxygen. Both phenomena can be exploited for quantitative O2 sensing. The respective sensor responses can be described by the same modified Stern‐Volmer model that distinguishes between accessible and non‐accessible luminescence centers or charge carriers, respectively. The impact of the temperature is studied in the range from room temperature up to 150 °C.

Edge Laplacians and Edge Poisson Transforms for Graphs - Arends, Christian; Frahm, Jan; Hilgert, Joachim (Potential Analysis)
Abstract For a finite graph, we establish natural isomorphisms between eigenspaces of a Laplace operator acting on functions on the edges and eigenspaces of a transfer operator acting on functions on one-sided infinite non-backtracking paths. Interpreting the transfer operator as a classical dynamical system and the Laplace operator as its quantization, this result can be viewed as a quantum-classical correspondence . In contrast to previously established quantum-classical correspondences for the vertex Laplacian which exclude certain exceptional spectral parameters, our correspondence is valid for all parameters. This allows us to relate certain spectral quantities to topological properties of the graph such as the cyclomatic number and the 2-colorability. The quantum-classical correspondence for the edge Laplacian is induced by an edge Poisson transform on the universal covering of the graph which is a tree of bounded degree. In the special case of regular trees, we relate both the vertex and the edge Poisson transform to the representation theory of the automorphism group of the tree and study associated operator valued Hecke algebras.

A pairing formula for resonant states on finite regular graphs - Arends, Christian; Frahm, Jan; Hilgert, Joachim (Mathematische Annalen)
Abstract On a finite regular graph, (co)resonant states are eigendistributions of the transfer operator associated to the shift on one-sided infinite non-backtracking paths. We introduce two pairings of resonant and coresonant states, the vertex pairing which involves only the dependence on the initial/terminal vertex of the path, and the geodesic pairing which is given by integrating over all geodesics the evaluation of the coresonant state on the first half of the geodesic times the resonant state on the second half. The main result is that these two pairings coincide up to a constant which depends on the resonance, i.e. the corresponding eigenvalue of the transfer operator.

The Effect of Compulsory Schooling on Vaccination Against COVID - Monsees, Daniel; Schmitz, Hendrik (Health Economics)
ABSTRACT We study the effect of education on vaccination against COVID in Germany in a sample of individuals above the age of 60. In ordinary least squares regressions, we find that, in this age group, one more year of education goes along with a 0.7 percentage point increase in the likelihood to get a COVID vaccination. In two stage least squares regressions where changes in compulsory schooling laws are used as exogenous variation for education, the effect of an additional year of education is estimated to be zero. The results hold for the compliers to the policy change which are older individuals at the lowest margin of education.

Gamification in der Förderung schriftsprachlicher Fähigkeiten - Motivationssteigerung durch spielerische Elemente in digitalen Anwendungen - Bodynek, Joanna (Praxis Sprache)

Birgit Aschmann / Klaus Herbers, Eine andere Geschichte Spaniens. Schlüsselgestalten vom Mittelalter bis ins 20.Jahrhundert. - Hansen, Christin (Historische Zeitschrift)

Im Todeswasser: Eine Metapher in der Hebräischen Bibel und im Werbespot ‚Der Weg‘ - Bergmann, Claudia Dorit (Weihnachts-Werbespots als moderne Krippenspiele)

Digitalität in der Theaterwissenschaft. Forum der AG ARCHIV mit NFDI4Culture - Ertel, Erhart; Lamb, Jochen; Münzmay, Andreas; Primavesi, Patrick; Probst, Nora; Rittershaus, David; Schäfer, Martin Jörg; Voß, Franziska (Matters of Urgency – Herausforderungen der Gegenwart in Theater und Wissenschaft)

Estimation of energy, economic and environmental efficiency for renovation of building heating system - Polyvianchuk, Andrii; Malyarenko, Vitaliy; Kapustenko, Petro; Polyvianchuk, Natalia; Petruk, Halyna; Arsenyeva, Olga (Clean Technologies and Environmental Policy)

Unterrichtsintegrierte Förderung von mathematischen Basiskompetenzen. Empirische Rekonstruktion interferierender Praktiken der Förderung im Mathematikunterricht der Grundschule - Häsel-Weide, Uta; Nührenbörger, M. (Zeitschrift für Grundschulforschung)

From belonging to success: Evaluating the influence of sense of belonging to physics on first-year university students’ academic outcomes and the benefits of a holistic support program - Feser, Markus Sebastian; Bauer, Anna Brigitte (European Journal of Physics)
Abstract The present study explored the role of first-year physics students’ sense of belonging to physics and how it relates to their learning progression in higher education-level physics. Conducted at Paderborn University, this study examined how students’ sense of belonging to physics influences their academic outcomes in an introductory experimental physics course. Additionally, we investigated how physics students’ engagement in the Physiktreff—a holistic support program for first-year physics students to help them cope with academic and social challenges during their studies—impacts the development of their sense of belonging to physics over time. Our findings indicated that students with a stronger sense of belonging to physics performed better academically. Moreover, students who actively participated in the support program experienced a positive shift in their sense of belonging to physics. However, our findings also revealed that physics students with a higher initial sense of belonging to physics tended to experience a decline in their sense of belonging to physics during their first semester. These results underscore the importance of fostering a sense of belonging to physics within higher education, particularly during the introductory phase of students’ studies.

Surface-Assisted Assembly of DNA Origami Lattices on Silicon Wafers - Parikka, Johannes; Pothineni, Bhanu Kiran; Järvinen, Heini; Tapio, Kosti; Keller, Adrian; Toppari, J. Jussi (Methods in Molecular Biology)

European Commonalities of Translation Strategies—A Diachronic Sketch - Albrecht, Jörn; Kunert, Irene Dorothea; Grzega, Joachim (The Routledge Handbook of Eurolinguistics)

„Der Tod tritt an jede Pritsche, an jede zerschlagene Fensterscheibe heran und fragt: 'Wann darf ich kommen?'“. Möglichkeiten und Grenzen des Sprechens über Tod und des sprachlichen Vollzugs von Trauer in Textkommunikaten des Gettos Litzmannstadt - Markewitz, Friedrich (Tod und Trauer – digital/analog)
Stets haben menschliche Gemeinschaften versucht, dem nahenden, sichvollziehenden sowie geschehenen Tod zu begegnen und dabei kommunikativePraktiken ausgebildet, die für die Zwecke der Todes- und Trauerverarbeitung zumEinsatz kommen. Die Erfassung und Reflexion dieser Praktiken ist Thema diesesBeitrags, in dem die extremen kommunikativen Ränder des sprachlichen Erfassensvon Tod sowie des performativen Vollziehens von Trauer während der Shoa reflek-tiert werden sollen. Als Grundlage dienen textuelle Kommunikate des Gettos Litz-mannstadt der Jahre 1941 bis 1944. Gefragt werden soll nach Mustern des Anzeigensvon Tod, Musteranschlüssen anhand von Personifikationen und Metaphorisierun-gen des Todes und nach Musterabbrüchen als Formen des Nicht-(Mehr)-Ausdrücken-Könnens.
Keywords: Gettokommunikation; Gettokommunikate; kommunikative Praktiken; Shoa; Unsagbarkeit

Heideggers Schweigen zur Shoa. Kommunikationsanalytische Reflexionen auf das invektive Potential von Schweigen - Markewitz, Friedrich (Glottotheory)
Ausgehend von der Konzeptualisierung der Shoa als kommunikativem Extremfall erweist sich nicht nur das erzwungene Schweigen jüdischer Shoa-Opfer und -Überlebender als so konstitutiv wie herausforderungsvoll, sondern ebenso das täterseitige Schweigen, als z.B. ein Die-eigene-Schuld-ignorieren-Wollen. Aber ebenso irritierend anmutende Formen des Schweigens indirekt zustimmender oder zumindest wegsehender Mitglieder der Integrierten Gesellschaft während und nach dem ‚Dritten Reich‘ sind in ihrer ethisch-normativen Eingebundenheit problematisch und zugleich bedenkenswert. So herausgehoben wie auffällig erscheint aus dieser Akteursgruppe der deutsche Philosoph Martin Heidegger, hätte dieser doch bis zu seinem Tod 1976 durchaus Gelegenheit gehabt, sich zum Zivilisationsbruch der Shoa zu äußern. Doch hat er, zumindest öffentlich, stets dazu geschwiegen. Dieses Schweigen soll im Rahmen dieses Beitrages hinsichtlich seines invektiven Potentials und in Bezug zu Heideggers eigenen (philosophischen) Ausführungen zum Schweigen reflektiert werden. Damit will der Beitrag zu einer linguistischen Aufarbeitung des Kommunikationsverhaltens Heideggers, der Ausdifferenzierung einer diskurslinguistischen Invektivitätsforschung und der Analyse des Kommunikationsphänomens ‚Schweigen‘ beitragen.
Keywords: Heidegger; Schweigen; Invektivität; Shoa

Langrezension zu Matthias Bau et al (Hg.) 'Vergessene Klassiker der Sprachwissenschaft? Zur Einführung und Erinnerung` - Markewitz, Friedrich (Zeitschrift für Rezensionen zur germanistischen Sprachwissenschaft)

Bewegung, Spiel und Sport im Ganztag - empirische Befunde zur Perspektive von Kindern - Neuber, Nils; Kaufmann, Nils; Kehne, Miriam; Noetzel, Ida; von Plettenberg, Elisabeth; Satzinger, Nicole; Schröder, Stefan; Süßenbach, Jessica (Potenziale von Bewegung, Spiel und Sport für ein gesundes Aufwachsen in Deutschland. Ergebnisse aus dem Projekt ,Move for Health')

Potenziale von Bewegung, Spiel und Sport für ein gesundes Aufwachsen in Deutschland

Data Quality in the Engineering of Circular Products - Decision support for circular value creation through data ecosystems - Gräßler, Iris; Rarbach, Sven; Pottebaum, Jens (Industry 4.0 Science)